IMEurope Marketing Plan - Padilla Dergal, Jose Guillermo (2012)
Nowadays in modern business-to-business (b2b) markets, developing marketing communications has become one of the key factors. Specially, if the firm is small and unknown in the market and is facing a highly competitive environment. Therefore it becomes essential to build a company image and increase awareness in the minds of their interest groups. The objective of this paper is to create an effective marketing communications plan for a British company called “Inventory Management Europe Ltd” (IMEurope), which aims to extend the contracts of computer parts to £150K per month and to extend the scraping business to £125K per month. Currently, IMEurope does not carry out any formal marketing plan, thus the purpose of this paper is to provide an insightful preliminary plan that can be developed and eventually executed. This marketing plan is an opportunity to assess the key marketing activities that IMEurope should deploy in their aim to acquire new customers, build stronger ties with the existing ones and boost the company’s image within the British and International Computer Service industry.